Deep mantle earthquakes linked to CO2 degassing at the Mid-Atlantic Ridge - Zhiteng Yu; Satish C. Singh; Cédric Hamelin; Léa Grenet; Marcia Maia; Anne Briais; Lorenzo Petracchini; Daniele Brunelli (Nature Communications)
Abstract Volatiles (CO2, H2O) play a fundamental role in mantle melting beneath ocean spreading centers, but what role they play during the melt migration remains unknown. Using seismological data recorded by ocean-bottom seismometers, here we report the presence of deep earthquakes at 10–20 km depth in the mantle along the Mid-Atlantic Ridge axis, much below the brittle-ductile boundary. Syntheses of regional basaltic rock samples and their geochemical analyses indicate the presence of an abnormally high quantity of CO2 (~0.4–3.0 wt%) in the primary melts. As the degassing of a high concentration of dissolved CO2 produces volume change, we suggest that deep earthquakes in the mantle result from the degassing of CO2. The large concentration of CO2 in the primitive melt will influence the presence of melt beneath the lithosphere-asthenosphere boundary at sub-solidus temperatures.